Mechanisms for employing modern technology in teaching and research in the humanities and applied sciences at the undergraduate level (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
This study aimed to introduce the mechanisms of employing modern technology in teaching and researching the humanities and applied sciences. It used the descriptive approach, and a survey of the literature that dealt with the subject in many sources, whether books, periodicals, or various websites and platforms in the International Information Network. It addressed the need to activate the role of technology in raising the level of quality of higher education and the urgent need for that in view of the current societal changes. She urged university faculty members to adopt modern technologies in classrooms, such as computers, data projectors, artificial intelligence applications, and others. The study concluded with many recommendations, including: The need to train faculty members and researchers on the use of these devices and equipment, and provide them with the digital skills necessary to employ modern technology in teaching and scientific research. Encouraging educational institutions to open up to and benefit from direct public group courses by holding seminars, lectures and workshops to identify them, coordinating and cooperating between higher education institutions and state institutions to support the design and dissemination of this type of courses and training faculty members in educational institutions on the strategies for designing and developing these courses.
Keywords: modern technologies; informatics; sciences research; humanities and applied